ALTITUDE-ZONE LAWS OF THE WATER-REGULATING ROLE OF CARPATHIANS FOREST SOILS - Oliynyk, V. S.; Tkachuk, O. M.; Blystiv, V. I. (Forestry and Forest Melioration, 2018)
Introduction Long-term forest hydrological researches in the mountain conditions of the Carpathians indicate that increasing of forest cover watershed and optimization of forest’s cover age structure play quite a significant role for strengthening protecting and adjusting forest properties in the context of increasing planting of older age in it, especially medieval and mature trees, and decreasing number of young trees. This is a very burning problem for integral part of Carpathian region – Precarpathian hills, where runoff occurs very often and causes intensive erosion processes because of a number of factors as antropogenic reduction of forest cover (to 30 %) and transformation its planting structure on large area by plowing (more than 40 %). The estimation of its modern conditions (percentage of forest cover, age structure of planting and forest categories) is a considerable precondition for optimization of forest cover of piedmont watersheds, leading to prevention of negative processes and effectuation its stock adjusting functions. Significant agricultural occupancy of Precarpathian region caused decreasing of forest cover of the region and the development of transformed agricultural fields of erosion processes from the forest ones. Materials and Methods Data of covered forest greenery in 1947 and 2010 years were taken for the analysis of forest cover watershed. First of them characterized forest cover at the beginning of intensive using of forest resources in 50-80 years of the last century. The second characterized the modern stage of forest using. Since 1947 indicators of forest cover watersheds have been borrowed from hydrological book of statistics and in 2010 years it was calculated by us on the basis of relational database of VO”Ukrderzhlisproekt”. The features of river basins forest cover of foothills are characterized in comparison to the neighbouring conditions of Precarpathian region. Results and Conclusions The dynamics of forest cover percentage, forest stands species and age structure of trees and forest categories watersheds is analyzed depending on its average height above sea level. The empirical formulas for the effect of watersheds forest cover increasing to improve rivers regime and enhance their underground supply are given. The ways of optimizing of Precarpathian hills forest cover are proposed to prevent the occurrence of surface water runoff and erosion development. Forest cover of river watershed of Precarpathian region is less than hydrological-efficient. However it is characterized by relatively favorable age and tree species structure of planting, which is able to improve regime of river flow and enlarge resources of underground water. With the purpose of optimization protective, especially it is necessary to increasing its forest cover, change of minor fir trees with root trees and increasing areas of protective forest categories due to decreasing part of operational ones. These measures one should dedicate to small watersheds with the area less than 100 square kilometers with not big regulation of water flow. The changes of power, rubbly, moisture resources and infiltration of forest soils under plantations of different ages in foothill and mountain forests are analyzed. The changes in water permeability of soils are characterized depending on the soils moisture. Permeability of soils of Carpathians depends on forest sites (types of soil), area covered by forests, age of planting and weather situations. Indexes of soil infiltration in mountain are in 2-3 times higher than in piedmont. They rise in both cases as age of planting increases. Soils infiltration decreases with the increase of their humidity. As a rule, this process proceeds faster on non-forest areas, some slower it is on areas after felling and in young stands. The least changes in soils permeability are in mature stands. Light-brown soils of beech belt are characterized by the best water-regulation properties, darkly-brown rubbly soils in spruce forests exhibit relatively good ones and brownified podzolic gleyed soils in the mixed forests of Precarpathian region are the less water-regulating.